2014
DOI: 10.1124/dmd.114.057885
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of 30 Murine Cytochrome P450 Genes Results In Viable Mice With Compromised Drug Metabolism

Abstract: In humans, 75% of all drugs are metabolized by the cytochrome P450-dependent monooxygenase system. Enzymes encoded by the CYP2C, CYP2D, and CYP3A gene clusters account for ∼80% of this activity. There are profound species differences in the multiplicity of cytochrome P450 enzymes, and the use of mouse models to predict pathways of drug metabolism is further complicated by overlapping substrate specificity between enzymes from different gene families. To establish the role of the hepatic and extrahepatic P450 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 45 publications
(63 reference statements)
2
14
0
Order By: Relevance
“…For example, mice with a knockout of the hepatic CYP reductase gene, required for the catalytic activity of CYPs, are viable [26, 27], thus indicating that CYPs involved in xenobiotic metabolism are not critical for reproduction and physiological homeostasis with minor alterations in liver function. More recently, in a monumental accomplishment, mice lacking almost all of the known xenobiotic-metabolizing enzyme members of the Cyp2c, Cyp2d, and Cyp3a gene clusters, a total of 30 genes, were created and these mice also were viable with a minor hepatic phenotype of unknown mechanism [28]. This latter study confirms and definitively established that the hepatic, non-mitochondrial CYPs are primarily involved in metabolism of foreign compounds and have no critical physiological role.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…For example, mice with a knockout of the hepatic CYP reductase gene, required for the catalytic activity of CYPs, are viable [26, 27], thus indicating that CYPs involved in xenobiotic metabolism are not critical for reproduction and physiological homeostasis with minor alterations in liver function. More recently, in a monumental accomplishment, mice lacking almost all of the known xenobiotic-metabolizing enzyme members of the Cyp2c, Cyp2d, and Cyp3a gene clusters, a total of 30 genes, were created and these mice also were viable with a minor hepatic phenotype of unknown mechanism [28]. This latter study confirms and definitively established that the hepatic, non-mitochondrial CYPs are primarily involved in metabolism of foreign compounds and have no critical physiological role.…”
Section: Introductionmentioning
confidence: 83%
“…The CYPs and phase 2 enzymes are ideally amenable to this technology since they are largely dispensible for normal development and physiological homeostasis. One or multiple enzymes can be disrupted and the mice are otherwise normal and can be used to study xenobiotic metabolism [28]. Similarly, the receptors such as AHR [84, 85], PXR [86, 87] and constitutive androstane receptor (CAR) [88] can be knocked out and the mice are viable, although abnormal immune, hepatic and reproductive phenotypes are present in the Ahr -null mice [84, 85].…”
Section: Expert Opinionmentioning
confidence: 99%
“…Nullizygous mouse models have become commonplace in toxicology research [1, 2], especially the use of xenobiotic receptor and Cyp subfamily-null mice [36]. These models are widely used in the study of the metabolism and distribution of pharmaceuticals and hazardous environmental chemicals [46].…”
Section: Introductionmentioning
confidence: 99%
“…However, in early clinical studies, the human value was found to be approximately of osimertinib in HLM was much greater than in MLM ( Figure 3A). To determine the reason for this species difference in metabolism, we analysed osimertinib stability in liver microsomes from Cyp2c, Cyp2d and Cyp3a gene cluster knockout mice, and from a combined Cyp2c/2d/3a triple-cluster knockout line (19)(20)(21)(22). Osimertinib stability was greatly increased in Cyp2d KO ( Figure 3A) and Cyp2c/2d/3a KO (not shown) microsomes but not in any of the other KO microsomes.…”
Section: Murine Cyp2d Are Responsible For the Species Difference In Omentioning
confidence: 99%
“…The generation and characterisation of Cyp2cKO, Cyp2dKO, Cyp3aKO, Cyp2c/2d/3aKO, hCYP2D6*2 and hPXR/hCAR/hCYP3A4/3A7 mice has been described previously (19)(20)(21)(22). For the humanized lines, briefly, the hCYP2D6*2 line contains a targeted insertion of an expression cassette containing 9kb of the CYP2D6 promoter, along with all exons, introns and 5' and 3' untranslated regions, into the murine Cyp2d locus, from which all nine functional murine Cyp2d genes have been deleted (20).…”
Section: Animal Lines and Husbandrymentioning
confidence: 99%